The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.1192/bjp.153.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Morbidity and Social Problems in Patients with Insulin-Dependent Diabetes Mellitus

Abstract: A two-stage screening strategy was used to study psychiatric morbidity and social problems in a consecutive series of out-patients with insulin-dependent diabetes mellitus. The prevalence of psychiatric morbidity was 18%, and consisted of depression, anxiety, and attendant symptoms. Patients reporting major social problems had significantly higher levels of psychiatric symptoms. Psychiatric morbidity was not associated with the presence of complications of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
21
2
3

Year Published

1990
1990
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 20 publications
5
21
2
3
Order By: Relevance
“…However, Bridges and Goldberg [17] reported a 39% rate in patients with neurological disorders and Surridge et al [5] reported varying figures (e.g., 60%) for patients who complained of fatigability and energy loss. It is difficult to attribute the high incidence of psychiatric morbidity in the present study to the degree of illness, because the mean age of our patients and the duration of DM were even less than that described in other studies [5,7]. There was also no positive correlation between the high morbidity and the number of hypoglycemic comas.…”
Section: Discussioncontrasting
confidence: 79%
See 4 more Smart Citations
“…However, Bridges and Goldberg [17] reported a 39% rate in patients with neurological disorders and Surridge et al [5] reported varying figures (e.g., 60%) for patients who complained of fatigability and energy loss. It is difficult to attribute the high incidence of psychiatric morbidity in the present study to the degree of illness, because the mean age of our patients and the duration of DM were even less than that described in other studies [5,7]. There was also no positive correlation between the high morbidity and the number of hypoglycemic comas.…”
Section: Discussioncontrasting
confidence: 79%
“…The prevalence of psychiatric morbidity in our diabetic patients is relatively high (44.7%), compared with, for example, the 18% reported by Wilkinson et al [7] and 11% for males and 26% for females cited by Hobbs et al [15]. Maguire et al [16] reported a 23% rate in a study of patients on general medical wards.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations